Tobacco harvest processing; physics overview and design of contextualized physics teaching materials - Inggita Sukma Anggreini; Supeno; Sulifah Aprilya Hariani; Fadiatul Hasinah Binti Muhammad; Handoyo Saputro; Iwan Wicaksono (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study aims to develop contextual-based physics teaching materials by integrating local wisdom from the processing of tobacco harvests in Jember, East Java, into junior high school science materials. The teaching materials are designed to promote critical thinking skills, including interpretation, analysis, evaluation, inference, and explanation. This research is motivated by the need to make physics learning more meaningful and relevant to students' daily lives. The research method used is research and development (R&D) with the ADDIE model, which focuses on the analysis and design stages. The teaching materials are presented interactively and visually using the Canva digital platform and can be accessed by students via an interactive website. Data analysis involved expert validation and questionnaire responses from 30 seventh-grade junior high school students. Expert validation was analyzed descriptively and quantitatively, and student responses were analyzed according to the frequency distribution of each aspect assessed. Experts' results of content validation show that teaching materials are suitable for learning. Based on the physics review, there are several tobacco processing processes related to physics concepts. The physics materials about temperature, heat transfer by conduction, convection, radiation, and specific heat directly relate to the real process of drying tobacco. Student responses were obtained through questionnaires and analyzed descriptively. The results showed that this contextual teaching material effectively increased students' learning motivation, concept understanding, and critical thinking skills. Students stated that the teaching materials were interesting, easy to understand, and related to their daily experiences. It can be concluded that local context-based physics teaching materials have strong potential to increase student engagement and support the development of thinking skills.